Dampak Doomscrolling Terhadap Subjective Wellbeing Mahasiswa Kampus 3 Universitas Islam Negeri Maulana Malik Ibrahim Malang - Najwa, Maulidya Nurin; Bilqisa, Salsabila (LoroNG: Media Pengkajian Sosial Budaya, 2025)
The advancement of digital technology has given rise to the behavior of doomscrolling, a habit of excessively consuming negative news on social media, which impacts students' well-being. This study analyzes the influence of doomscrolling on the subjective well-being of students at Campus 3 of UIN Maulana Malik Ibrahim Malang, who experience limited social activity. The research employs a quantitative approach with a non-experimental correlational design. Data were collected through an online questionnaire using a Likert scale, consisting of 20 items measuring doomscrolling intensity and 12 items measuring subjective well-being. Regression analysis results show that doomscrolling negatively affects subjective well-being, with a significance value of 0.005 and an R² of 0.038. This indicates that the higher the level of doomscrolling, the lower the subjective well-being experienced by students. These findings highlight the importance of digital literacy and self-regulation in social media usage. The study also recommends campus interventions through digital well-being training and the enhancement of positive social activities to reduce exposure to negative content. In conclusion, although the influence is small, doomscrolling remains a significant factor in the decline of students' psychological well-being.